“Superman’s Editor Mortimer Weisinger”: the Success and Extension of the Superman Brand in the Silver Age of Comics - (:unkn) unknown (My University, 2017)
My thesis examines the career of Detective Comics’ editor Mortimer Weisinger from 1957-1970, during which time Superman transitioned from a simple character to a complex brand. It details the creation of the character and subsequent growth into multiple mediums. Weisinger’s greatest contribution to the hero was an extended mythology and spin-off comic series. I analyze these series, as well as his other editorial tendencies, to understand the business strategies and management of the Superman brand. Another interest in this thesis is comic book fandom, as feedback from fans allowed National’s management to identify trends. Weisinger’s involvement with early science fiction fan communities preceded his career as an editor, putting him in a unique position as a fan that turned their passion into a career. His management of the Superman line of comics informed the treatment of superhero brands today.
Keywords: Comic Books; Franchising; Mortimer Weisinger; Silver Age of Comics; Superman; Transmedia